Role of Family in Addictive Disorders - Mathew, K.J.; Regmi, Bibhushan; Lama, Lopsang Dinchen (International Journal of Psychosocial Rehabilitation, 2018)
Addictive behaviors are found to be more prevalent among some families in various forms. Although many explanations are provided, there may be various factors and forces associated with family in the ini- tiation, maintenance and recovery of addictive disorders. Modelling, poor parenting skills, structural and relationship issues, support, sociocultural frame work and socio economic status of the family may play different roles in various aspects of addictive disorders. Comprehensive understandings of such factors are important to deal with the problem of addictive behaviors in various stages and also for prevention.An appropriate concern and participation of family may lead to better outcomes.